When “good” is not always right: effect of the consequences of motor action on valence-space associations - Brouillet, Denis; Milhau, Audrey; Brouillet, Thibaut (Frontiers in Psychology, 2015)
Since the work of Casasanto (2009), it is now well established that valence and laterality are associated. Participants tend to prefer objects presented on their dominant side over items presented on their non-dominant side, and to place good items on their dominant side and bad items on the other side. Several studies highlight that those associations of valence and laterality are accounted for by the greater motor fluency of the dominant hand and various studies noted that these associations could be reversed depending on the way people interact with their environment. Consistently with the Theory of Event Coding, the aim of this work is to show that the consequences of motor actions could also reverse the associations between valence and laterality. Thus, if participants had to place two animals (one good, one bad) on two supports, one stable (no risk of falling), one unstable (risk of falling), we hypothesized that the good item would be placed on the stable support, regardless of the side where it would be put (i.e., on the dominant or non-dominant side). We expected the opposite for the bad item. The results of two experiments are consistent with this prediction and support the claim that the consequences of motor action bias the hedonic connotation of our dominant side.